Social Empowerment Programs: The Role of Administrative Leadership in Increasing the Knowledge and Attitudes of Qatari Youth Toward Entrepreneurial Projects in Qatar - Al-kuwari, Zainab Abdullah (Journal of Ecohumanism, 2025)
This qualitative research aims to evaluate the integration of entrepreneurial projects within social empowerment programs in Qatar, assess public awareness of these programs, and analyze the role leaders play in shaping perceptions. It further seeks to examine the effectiveness, benefits, and importance of the courses offered to participants, gauge youth interest in engaging with these programs, and determine how well entrepreneurial project courses address the challenges faced by the Qatari public, while also identifying their key advantages. Semi-structured and in-depth interviews were conducted with 15 individuals, selected for their direct involvement or experience with entrepreneurial projects and social empowerment programs. The research yielded several important findings. Leaders were found to play a significant role in influencing social empowerment programs. The research highlighted the importance of providing practical, specialized training to equip young people for entrepreneurial ventures and underscored the need for spreading knowledge and awareness, which are crucial for successful entrepreneurship. Easy access to information and resources related to social empowerment programs significantly enhances the ability of youth to make informed decisions. Additionally, the study emphasized the value of practical experiences that align with real-world applications, facilitating the transition from theory to practice. Furthermore, the findings revealed the need for robust evaluation mechanisms and ongoing support systems to continuously improve programs aimed at preparing young people for entrepreneurial endeavors, as sustained guidance and follow-up services are vital for entrepreneurial success